Ligated Transition Metal Clusters in Solid-state Chemistry The legacy of Marcel Sergent - Halet, Jean-François (Structure and Bonding,, 2019)
This volume dedicated to the memory of Marcel Sergent who was a leader in this field for many years, addresses past achievements and recent developments in this vibrant area of research. Large classes of ligated transition metal clusters are produced either exclusively or most reliably by means of high-temperature solid-state reactions. Among them, the Chevrel-Sergent phases and related materials have generated enormous interest since their discovery in 1971. Today, these materials and their numerous derivatives still constitute a vivid area of research finding some applications not only in superconductivity, but also in catalysis, optics or thermoelectricity to mention a few. .